2018
DOI: 10.14712/23362189.2018.860
|View full text |Cite
|
Sign up to set email alerts
|

Learning with Mobiles in the Digital Age

Abstract: Personal mobile devices are central to the current digital age, and will soon be pervasive and ubiquitous, and unremarkable in most of the world’s societies and cultures. They are central to the educational futures for the digital age, to both in theory and practice. They are, however, not straightforward. Whilst the relationships of these technologies to formal education and its professions and institutions, conceptualised as ‘mobile learning’, seemed straightforward, it has also become increasingly marginal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 52 publications
1
17
0
2
Order By: Relevance
“…However, ongoing research point to the myriad of potential benefits of integrating mobile phones use for teaching and learning including mobile learning, inquiry-based learning, the use of learning pedagogies such as smart mobile methods TPACK (Ahmad, 2018; Almaiah and Alismaiel, 2019; Kukulska‐Hulme and Viberg, 2018; Traxler, 2018) to stimulate collaboration and engagement.…”
Section: Introductionmentioning
confidence: 99%
“…However, ongoing research point to the myriad of potential benefits of integrating mobile phones use for teaching and learning including mobile learning, inquiry-based learning, the use of learning pedagogies such as smart mobile methods TPACK (Ahmad, 2018; Almaiah and Alismaiel, 2019; Kukulska‐Hulme and Viberg, 2018; Traxler, 2018) to stimulate collaboration and engagement.…”
Section: Introductionmentioning
confidence: 99%
“…But the pressures for scale and sustainability, on and from these agencies and ministries, expressed as 'system strengthening' and 'service delivery', reinforced traditional didactic teaching based on schools and content, but not so much on livelong, adult or informal learning, nor for marginal, peripheral or indigenous communities and their languages. Looking at the impact of 'mobile learning' on mother tongues, indigenous cultures and nomadic peoples; or even just those countries, communities and individuals away from the large, the norm and the mainstream, we conclude that 'mobile learning' is skewed away from these countries, communities and individuals, and instead is usually skewed in favour of Anglophone American interests or the global North more generally [39,40].…”
Section: Background: the Established Mobile Learning Paradigmmentioning
confidence: 89%
“…Authors still refine their definitions of 'mobile learning', but our worry is that these all treat learning itself as unchanged and unchallenged [42]. While there is a plethora of different definitions, some key characteristics can be identified, namely that learning can be extended in terms of its reach or catchment and enhanced and enriched in terms of its experience [39] Implicit in these definitions is however little evidence that learning itself is changing as the nature of society changes together with its relation to technology within it. This is a key difference between the established 'mobile learning' paradigm and a world where mobiles, mobility and connectedness change what is learnt, how it is learnt, who it is learnt from, why it is learnt, where it is learnt and how this learning is used and valued, essentially how mobiles, mobility and connectedness change the epistemological foundations of our worlds and cultures.…”
mentioning
confidence: 99%
“…Biggs and Justice (2011) indicated that it is a learning delivery method using mobile technology. Traxler (2018) highlights mobile learning as any kind of educational facility where handheld or palmtop devices play the sole or dominant role. Andronico et al (2003) highlights that it is any method of learning or teaching and studying which carries out in a mobile environment or with the use of a mobile device, such as smart phones, tablet PCs, etc.…”
Section: Mobile Learningmentioning
confidence: 99%